Smärtpatienter – personlighet, upplevt sammanhang, kliniskt status, effekter av kognitiv terapi - Peilot, Birgitta; Samuelsson, Anita; Petterson, Sven; Norberg, Eva Marie; Frodi, Ann (Socialmedicinsk tidskrift, 2007)
Vad är det som påverkar en individs upplevelse av och förmåga att hantera stress och smärta? Trots att forskningen kring långvarig smärta, dess orsaker och konsekvenser länge har varit intensiv och numera ses ur ett biopsykosocialt perspektiv, kvarstår frågor om vilka faktorer som styr människors smärtupplevelse och ibland gör att smärtan blir långvarig och svårbehandlad. Denna artikel är en sammanställning av det examensarbete som författarna gjorde i samband med legitimationsgrundande utbildning i Kognitiv Psykoterapi vid Cognitivt Center i Kungälv 2005. I studien undersöktes sambandet mellan långvarig smärta och sårbarhetsfaktorer samt effekter av kognitiv terapi utifrån en kvantitativ och kvalitativ eftermätning avseende kliniskt status. The current study had 3 parts: 1a) A group of patients with stress related pain (assessed on a VAS-scale) was compared to a control group on personality profile (Scandinavian Universities Personality Scales), Sense of Coherence (SOC/KASAM), as well as clinical status: Relationship Styles (RSQ), depression (Beck Depression Inventory/BDI) and anxiety (Beck’s Anxiety Scale/BAI); 1b) the effects of cognitive psychotherapy on clinical status were assessed following treatment; and 2), interviews were conducted with a subgroup of the pain patients focusing on significant aspects of the therapy process. The Study 1a results indicated that patients with pain exhibited significantly more Somatic and Mental Stress propensity, Vulnerability to stress, Sensation seeking, Bitterness, and Distrust than the control group. In addition, they displayed significantly more “Preoccupied attachment”, less optimal Sense of Coherence, more depression and anxiety symptoms. Following treatment (Study 1b), pain patients showed a significant decrease in depression and pain, particularly among females. Study 2 interview data suggested a process going from chaos and powerlessness to an increased awareness, knowledge, and ability to look forward. Clinical implications are discussed. Keywords: Pain, psychopathology,attachment, sense of coherence(SOC), cognitive therapy